2000
DOI: 10.1523/jneurosci.20-22-08344.2000
|View full text |Cite
|
Sign up to set email alerts
|

Mismatched Appositions of Presynaptic and Postsynaptic Components in Isolated Hippocampal Neurons

Abstract: To determine whether presynaptic input is necessary for postsynaptic differentiation, we isolated hippocampal neurons in microisland culture and thus deprived pyramidal cells of GABA input and GABAergic neurons of glutamate input. We find that glutamate input is necessary for clustering the AMPA-type glutamate receptor but not for clustering the NMDA receptor or the associated PSD-95 family scaffold in GABAergic cells; GABA input is not necessary for clustering the GABA A receptor or gephyrin in pyramidal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
100
3

Year Published

2001
2001
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 67 publications
(77 reference statements)
12
100
3
Order By: Relevance
“…Nevertheless, immunolabeling with synaptic vesicle markers synaptophysin and SV2 suggested that GABA A R clusters were frequently localized to sites of presynaptic contacts (data not shown). This result and the observed presence of GABA A R clusters in single-cell cultures of glutamate neurons apposed to autaptic glutamate containing terminals shown by Rao et al (2000) and confirmed in our laboratory (data not shown) indicate that small GABA A R clusters can form in the absence of any GABAergic innervation, although they are frequently associated with other presynaptic contacts.…”
Section: Two Types Of Gabasupporting
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, immunolabeling with synaptic vesicle markers synaptophysin and SV2 suggested that GABA A R clusters were frequently localized to sites of presynaptic contacts (data not shown). This result and the observed presence of GABA A R clusters in single-cell cultures of glutamate neurons apposed to autaptic glutamate containing terminals shown by Rao et al (2000) and confirmed in our laboratory (data not shown) indicate that small GABA A R clusters can form in the absence of any GABAergic innervation, although they are frequently associated with other presynaptic contacts.…”
Section: Two Types Of Gabasupporting
confidence: 80%
“…A population of small GABA A R clusters associate with glutamatergic synapses in pyramidal neurons receiving both glutamatergic and GABAergic innervation Recently, Rao et al (2000) reported that microcultures of isolated glutamatergic pyramidal neurons, where no GAD-containing synapses were present, showed mismatched GABA A R clusters localized postsynaptically to synaptic vesicle-containing terminals, presumably containing glutamate. We tested whether this was an anomalous situation that occurs only in the total absence of GABAergic innervation or if this also occurs in pyramidal cells that receive both GABAergic innervation from interneurons and glutamatergic innervation from themselves (autapses) and other pyramidal cells.…”
Section: A Bgh Empty Arrowheads)mentioning
confidence: 99%
“…Hippocampal sections were stained for GAD65, the synthetic enzyme for GABA, which is known to be concentrated in the synaptic terminals of GABAergic neurons [4,23,26]. Punctate GAD65 immunostaining formed a dense network in the dentate granule cell layer and inner molecular layer, and less staining in the outer molecular layer of the dentate gyrus.…”
Section: Distribution Of Gad65 and Gephyrinmentioning
confidence: 99%
“…For example, microisland cultures containing only a single autaptic neuron or a few neurons have been widely used to study molecular and cellular mechanisms of synaptic transmission and synaptic plasticity. [12][13][14][15][16][17][18] With the usually low efficiency of 1-5%, Ca 2+ -phosphate transfection is not suitable for transfecting single autaptic neurons to study gene functions. In order to transfect single autaptic neurons in microisland cultures, the transfection efficiency has to be greatly improved.…”
Section: Introductionmentioning
confidence: 99%